Accuracy of transrectal ultrasound guided prostate biopsy: Histopathological correlation to matched prostatectomy specimens - ÇAM, HAYDAR KAMİL; YÜCEL, SELÇUK (BLACKWELL PUBLISHING ASIA, 2002)
Background: The Gleason grading system is currently the world's most commonly used histological system for prostate cancer. It provides significant information about the prognosis. Therefore, Gleason score is accepted as an important factor in therapeutic decision-making for prostate cancer. This retrospective study assessed the correlation of transrectal ultrasound (TRUS) guided biopsy and radical prostatectomy specimens in terms of Gleason scores. Methods: We reviewed the records of 103 patients who underwent radical prostatectomy due to clinically localized prostate cancer. The Gleason scores of the TRUS biopsies were compared with the respective Gleason scores of surgical specimen. Results: In 28.7% of cases, the TRUS biopsy score was the same as that of the radical prostatectomy specimen. The most significant discordance was the upgrading of well-differentiated tumors after surgery in 71.7% of cases. However, in 81.8% of cases with high Gleason score on TRUS, biopsy was correlated with poorly differentiated tumor after surgery. Conclusions: Well-differentiated tumors on TRUS biopsy did not correlate with the grades of final pathology in the majority of cases; however, a high Gleason score on TRUS biopsy usually indicated a poorly differentiated tumor on prostatectomy specimen. Therefore, the treatment algorithms for particularly well-differentiated tumors should not be deduced from biopsy histology alone.
Keywords: biopsy; Gleason score; prostate cancer; transrectal ultrasonography; CURRENT PROGNOSTIC FACTORS; GLEASON SCORE; NEEDLE-BIOPSY; CANCER; DIAGNOSIS